Improved Authentication in Information Systems through a Mobile Identity Management Scheme (MoIdM-MSS) Utilizing Mobile Signature Service - Sharifpour, Mohammadjavad; Shajari, Mehdi; Asghari Tochae, Seyyed Amir (EAI Endorsed Transactions on Scalable Information Systems, 2025)
In today's digital economy, work processes are increasingly digitized using computer information systems. An essential aspect of employees' reliance on these systems is trust in their reliability. Mobile devices and apps play a vital role in this digital landscape, with Mobile Identity at the forefront. Mobile Identity extends the concept of digital identity through mobile networks, acting as a tool for login and transactions and as a crucial element in communication and interaction. This paper introduces a Mobile Identity Management Scheme based on the Mobile Signature Service for information systems. The scheme enables digital signatures on mobile devices for various purposes, enhancing security by leveraging the user's private key and the system's authentication challenge. Through this approach, authentication is ensured by permitting only users with the correct private key to sign the challenge, eliminating the necessity for traditional authentication methods such as usernames and passwords.Furthermore, the scheme leverages mobile device security features like secure computing environments and biometric authentication to bolster authentication. By adding an extra layer of protection and focusing on user convenience, security is heightened without introducing unnecessary complexity. Evaluations conducted in local signing scenarios have demonstrated the scheme's effectiveness, acceptance, and potential, indicating promising results for its application in enhancing work process security.
Keywords: Mobile Identity Management; Mobile IdM; Mobile ID; Mobile Signature Service; MSS; Information Systems; Technology Acceptance Model; TAM